Geotechnical Engineering Challenges to Meet Current and Emerging Needs of Society - Nuno Guerra; Manuel Matos Fernandes; Cristiana Ferreira; António Gomes Correia; Alexandre Pinto; Pedro Sêco Pinto (CRC Press, 2024)
‘Geotechnical Engineering Challenges to Meet Current and Emerging Needs of Society'includes the papers presented at the XVIII European Conference on Soil Mechanics and Geotechnical Engineering (Lisbon, Portugal, August 26 to 30th, 2024). The papers aim to contribute to a better understanding of problems and solutions of geotechnical nature, as well as to a more adequate management of natural resources. Case studies are included to better disseminate the success and failure of Geotechnical Engineering practice. The peer-reviewed articles of these proceedings address the six main topics: New developments on structural design Geohazards Risk analysis and safety evaluation Current and new construction methods Environment, water, and energy Future city world vision With contributions from academic researchers and industry practitioners from Europe and abroad, this collection of conference articles features an interesting and wide-ranging combination of innovation, emerging technologies and case histories, and will be of interest to academics and professionals in Soil Mechanics and Geotechnical Engineering.